THE FOURTH ORDER MIXED PERIODIC RECURRENCE FRACTIONS - A.V. Semenchuk; R.A. Zatorsky (Vasyl Stefanyk Precarpathian National University, 2015)
Offered economical algorithm for calculation of rational shortenings of the fourth-order mixed periodic recurrence fraction.